Ethical Justification of Involving Human Volunteers in Phase 1 Trials - Rafique, Zoheb (Bangladesh Journal of Bioethics, 2017)
Tremendous development in recent medical science and the consequent discoveries resulting in successful prevention and also cure of different diseases are shared by clinical research involving the human volunteers. Preceding the trials in the human subjects, and to ensure safety, the proposed drug and other interventions are either tested in animals (vivo) or in laboratory (vitro) to evaluate initial safe starting dose for the human beings and to key out the benchmarks for the clinical monitoring for the potential unfavorable effects. These pre human trials might not necessarily protect against the untoward effects in the human beings as happened in the case of thalidomide tragedy, which caused disability and killed thousands of babies born to the mothers, those who took this medicine. Use of healthy human volunteers in the preliminary experiments or phase I clinical trials either reduces or excludes risks of subsequent undesirable effects in the future trails (1). Phase-1 trials are conducted in order to test the safety, reactions and immunogenicity of vaccines in volunteers. Novel treatments for the cancer are first tested in phase 1 trials enrolling the patients with advanced disease, who have exhausted the standard treatment options. Phase-1 oncology trials are the pivot point in the translation of new cancer therapies from bench to bedside. Nevertheless, these trials remain ethically controversial. The controversy stems from the fact that, classically, phase-1 oncology clinical trials involve first-in-human testing of experimental treatment candidates in patients with a terminal diagnosis, who typically have exhausted standard treatment options. Commentators on the ethics of phase-1 clinical trials make diametrically opposed claims about the prospect of direct medical benefit from participation in these trials-benefits that can be attributed to receiving the experimental treatment intervention. One camp of benefit skeptics, inhabited mainly by bioethicists, characterizes this form of research as lacking any reasonable prospect of direct medical benefit. They see an ethical cloud hovering over phase-1 trials, because the vast majority of patients volunteer for phase-1 trials out of a motivation to receive medical benefit. In the view of these skeptics, such patients therefore harbor a therapeutic misconception about research participation. This misconception calls into question the validity of informed consent and thereby undercuts the ethical basis of these trials (2). In this paper, I will discuss the ethical justification of the participation of human volunteers in phase-1 trials.